2020
DOI: 10.1080/14686996.2020.1722740
|View full text |Cite
|
Sign up to set email alerts
|

Progress on highly proton-conductive polymer thin films with organized structure and molecularly oriented structure

Abstract: Several current topics are introduced in this review, with particular attention to highly protonconductive polymer thin films with organized structure and molecularly oriented structure. Organized structure and molecularly oriented structure are anticipated as more promising approaches than conventional less-molecular-ordered structure to elucidate mechanisms of high proton conduction and control proton conduction. This review introduces related polymer materials and molecular design using lyotropic liquid cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 117 publications
1
20
0
Order By: Relevance
“…In recent years, researchers have continued to develop proton exchange materials with excellent properties and low prices to replace the Nafion materials, such as conductive polymer materials, conductive inorganic materials, solid electrolytes, flexible polymers, etc. However, these materials have certain shortcomings in terms of stability, and their performance will be reduced under long-term use.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have continued to develop proton exchange materials with excellent properties and low prices to replace the Nafion materials, such as conductive polymer materials, conductive inorganic materials, solid electrolytes, flexible polymers, etc. However, these materials have certain shortcomings in terms of stability, and their performance will be reduced under long-term use.…”
Section: Introductionmentioning
confidence: 99%
“…A slightly stronger peak occurs for CTA/PTZA–20 due to the organized aromatic triazole structure. The high proton conductivity has been accomplished with an ordered crystalline polymeric structure because the long‐range molecular ordered structure tends to allow passage of protons 32 …”
Section: Resultsmentioning
confidence: 99%
“…This grain distribution can be recognized as the dominant and most common. On the other hand, it was observed that lamellar polycrystalline microstructures are also often encountered and desirable due to their strength, toughness, plasticity, and creep resistance properties [51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%